Phosphate solubilization potential and stress tolerance of rhizobacteria from rice soil in Northern Thailand - Chaiharn, Mathurot; Lumyong, Saisamorn (World journal of microbiology & biotechnology, 2009)
Plant growth-promoting rhizobacteria (PGPR) are known to influence plant growth by various direct or indirect mechanisms. A total of 216 phosphate-solubilizing bacterial isolates were isolated from different rice rhizospheric soil in Northern Thailand. These isolate were screened in vitro for their plant growth-promoting activities such as solubilization of inorganic phosphate, ammonia (NH₃), catalase and cell wall-degrading enzyme activity. It was found that 100% solubilized inorganic phosphate, 77.77% produced NH₃ and most of the isolates were positive for catalase. In addition, some strains also produced cell wall-degrading enzymes such as protease (7%), chitinase (1%), cellulase (3%) and β-glucanase (3%), as evidenced by phenotypic biochemical test and quantitative assay using spectrophotometry. The isolates could exhibit more than two or three plant growth-promoting (PGP) traits, which may promote plant growth directly or indirectly or synergistically. Part of this study focused on the effect of NaCl, temperature, and pH on a specific the bacterial isolate Acinetobacter CR 1.8. Strain CR 1.8 was able to grow on up to 25% NaCl, between 25 and 55°C, and at pH 5-9. Maximum solubilization of tricalcium phosphate and aluminium phosphate was obtained at neutral pH, and 37°C. Strain CR 1.8 had protease activity but no cellulase, β-glucanase and cellulase activities.